Expression of R345W-Fibulin-3 Induces Epithelial-Mesenchymal Transition in Retinal Pigment Epithelial Cells - Zhou, Mi; Weber, Sarah R.; Zhao, Yuanjun; Chen, Han; Barber, Alistair J.; Grillo, Stephanie L.; Wills, Carson A.; Wang, Hong Gang; Hulleman, John D.; Sundstrom, Jeffrey M. (Frontiers in Cell and Developmental Biology, 2020)
Purpose: To investigate the role of protein misfolding in retinal pigment epithelial (RPE) cell dysfunction, the effects of R345W-Fibulin-3 expression on RPE cell phenotype were studied. Methods: Primary RPE cells were cultured to confluence on Transwells and infected with lentivirus constructs to express wild-type (WT)- or R345W-Fibulin-3. Barrier function was assessed by evaluating zonula occludens-1 (ZO-1) distribution and trans-epithelial electrical resistance (TER). Polarized secretion of vascular endothelial growth factor (VEGF), was measured by ELISA. Differentiation status was assessed by qPCR of genes known to be preferentially expressed in terminally differentiated RPE cells, and conversion to an epithelial-mesenchymal transition (EMT) phenotype was assessed by a migration assay. Results: Compared to RPE cells expressing WT-Fibulin-3, ZO-1 distribution was disrupted and TER values were significantly lower in RPE cells expressing R345W-Fibulin-3. In cells expressing mutant Fibulin-3, VEGF secretion was attenuated basally but not in the apical direction, whereas Fibulin-3 secretion was reduced in both the apical and basal directions. RPE signature genes were downregulated and multiple genes associated with EMT were upregulated in the mutant group. Migration assays revealed a faster recovery rate in ARPE-19 cells overexpressing R345W-Fibulin-3 compared to WT. Conclusions: The results suggest that expression of R345W-Fibulin-3 promotes EMT in RPE cells.